John the Baptist in history and theology - Marcus, Joel, 1951- (Columbia, South Carolina : The University of South Carolina Press, 2018)
An analysis that challenges the conventional Christian hierarchy of John the Baptist and Jesus of Nazareth.
APPENDIX 5 The "Others" in Josephus, Antiquities 18.118APPENDIX 6 Knut Backhaus's Interpretation of Acts 19:1-7; APPENDIX 7 The "Day-Baptists"; APPENDIX 8 John the Baptist's Use of Isaiah 40:3; APPENDIX 9 The Baptist in the Slavonic Version of Josephus's Jewish War; APPENDIX 10 Apocalyptic Belief and Perfectionism; APPENDIX 11 The Meaning of "Purification" in John 3:25; LIST OF ABBREVIATIONS; NOTES; GLOSSARY; BIBLIOGRAPHY; INDEX OF MODERN AUTHORS; SUBJECT INDEX; INDEX OF ANCIENT SOURCES
Includes bibliographical references.
Print version record and CIP data provided by publisher; resource not viewed.
Master record variable field(s) change: 072
Keywords: John, -- the Baptist, Saint; John, -- the Baptist, Saint; RELIGION / Christian Theology / Christology; RELIGION / Biblical Biography / New Testament; Electronic books